Service Quality of Public Technical Vocational Education and Training Colleges in South Africa: Customer Expectations and Perceptions - Nkululeko Praise God ZUNGU; Lawrence Mpele LEKHANYA (Journal of Economics and Behavioral Studies, 2018)
The focus of this survey is to seek the amount of the customers’ expectations levels of service quality in the public Technical Vocational Education and Training (PTVET) sector. The aim of this study was to examine and determine the expectations and perceptions levels of service quality provided by PTVET colleges, in order to achieve desired outcomes, and the survey followed SERQUAL model. Questionnaires were distributed to the 403 participants from selected PTVET in the Kwa-Zulu- Natal province. The study used a mix approach of systematic and quota sampling techniques. SPSS (25.0) version was employed for data analysis. The results of this study discovered that customers had higher service quality expectations (0,908 Cronbach's Alpha) compared to the service quality perceptions (0,923 Cronbach's Alpha) at the selected PTVET colleges, on all five service quality dimensions that were used to evaluate the expectations of service quality. This survey will benefit Rectors/Campus Managers for TVET colleges and to those who want to open their TVET colleges, because it will be used as a guide tool for them on how they can improve service quality strategy to differentiate themselves from their competitors. The findings are limited by the study’s exploratory, quantitative nature and small sample. Generalisation should be done with care and further research, with a large sample and consideration of other provinces, it therefore recommended.